PEMAHAMAN MANAJEMEN RUMAH SAKIT TENTANG PENTINGNYA KINERJA LINGKUNGAN DALAM PEMBANGUNAN BERKELANJUTAN - Sofiati Wardah; Yuli Astini (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This study aims to determine the understanding of hospital management on the importance of environmental performance in sustainable development and environmental management accounting information required in environmental management. Data were collected through questionnaires distributed to the management or waste management officers of each state and private hospitals in Mataram City. The data analysis technique used is descriptive analysis method. The results showed that hospital management has understood the importance of environmental performance in sustainable development and environmental management accounting information required by hospital management in the form of physical information and monetary information/cost, among others, the percentage of materials obtained from recycling, the amount of energy consumed and saved, the amount of water obtained from nature and wasted, the amount of waste treated and disposed of, the cost of evaluating and selecting environmental control equipment, the cost of developing/designing process/environmentally friendly products, the cost of training the employees for environmental issues, the cost of developing the environmental management system, inspectors of production processes to ensure compliance with environmental regulations, emission test costs, wastewater inspection fees, processing fees and disposal of hazardous waste, maintenance costs of waste treatment equipment, and polluted environmental cleaning costs.